Concerns Unleashed: Trajectories and Political Culture of Radicalization Within the Student Movement of San Marcos during the 1980s - Medina Montes, José Carlos (2025)
In this text, we describe and analyze the radical political culture among left-wing student activists at the National University of San Marcos (UNMSM) during the 1980s, exposing the way in which student political cadres became involved and consolidated their position, as well as the limitations and critical scenarios that led to the end of the political culture they had built. Using a qualitative analysis methodology, we conducted fourteen semi-structured interviews with former student leaders at UNMSM. We found that the interviewees contributed to the reproduction of an infrastructure of epochal dissent whose cultural basis was a structure of class-based sentiment in its late phase.